CD4+/CD8+ ratio, age, and risk of serious noncommunicable diseases in HIV-infected adults on antiretroviral therapy. (27th March 2016) - Castilho, Jessica L.; Shepherd, Bryan E.; Koethe, John; Turner, Megan; Bebawy, Sally; Logan, James; Rogers, William B.; Raffanti, Stephen; Sterling, Timothy R.
Abstract : Objective: In virologically suppressed HIV-infected adults, noncommunicable diseases (NCDs) have been associated with immune senescence and low CD4 + /CD8 + lymphocyte ratio. Age differences in the relationship between CD4 + /CD8 + ratio and NCDs have not been described. Design: Observational cohort study. Methods: We assessed CD4 + /CD8 + ratio and incident NCDs (cardiovascular, cancer, liver, and renal diseases) in HIV-infected adults started on antiretroviral therapy between 1998 and 2012. Study inclusion began once patients maintained virologic suppression for 12 months (defined as baseline). We examined age and baseline CD4 + /CD8 + ratio and used Cox proportional hazard models to assess baseline CD4 + /CD8 + ratio and NCDs. Results: This study included 2006 patients. Low baseline CD4 + /CD8 + ratio was associated with older age, male sex, and low CD4 + lymphocyte counts. In models adjusting for CD4 + lymphocyte count, CD4 + /CD8 + ratio was inversely associated with age ( P  < 0.01). Among all patients, 182 had incident NCDs, including 46 with coronary artery disease (CAD) events. CD4 + /CD8 + ratio was inversely associated with risk of CAD events [adjusted HR per 0.1 increase in CD4 + /CD8 + ratio = 0.87, 95% confidence interval (CI): 0.76–0.99, P  = 0.03]. This association was driven by those under age 50 years (adjusted HR 0.83 [0.70–0.97], P  = 0.02) vs. those over age 50 years (adjusted HR = 0.96 [0.79–1.18], P  = 0.71). CD4 + /CD8 + ratio was not significantly associated with incident noncardiac NCDs. Conclusions: Higher CD4 + /CD8 + ratio after 1 year of HIV virologic suppression was independently predictive of decreased CAD risk, particularly among younger adults. Advanced immune senescence may contribute to CAD events in younger HIV patients on antiretroviral therapy.